Redox Potential and Its Control in Research and Commercial Wine Fermentations - James Nelson; Roger Boulton; André Knoesen (Fermentation)
Redox potential is a solution property that influences specific yeast and bacterial activities and the rate of fermentation completion. There is a need to control it if reproducible fermentation outcomes are to be achieved and reliable conclusions are drawn at both the research and commercial scale of wine fermentation. Desirable outcomes that have been observed so far in wine fermentation include the prevention of sluggish and incomplete fermentations, an enhancement in cell viability, increases in the maintenance rate of non-growing cells, and the avoidance of hydrogen sulfide formation when elemental sulfur is present. Other expected fermentation outcomes include changes in the ratios of glycerol and succinate to ethanol, certain aroma and flavor components, and sulfite formation from sulfate in the juice. The juice composition determines the redox potential’s initial value, and the yeast strain’s interaction with the changing juice composition determines the pattern of the potential during fermentation. This interaction also establishes the dynamic response of the prevailing redox buffer to disturbances and the ability to control the potential during fermentation. The chemical reaction sequence, entities, and speciation thought to be responsible for establishing the redox potential in juices and wine are described. A quantitative model for control purposes remains elusive. Examples of the role of added iron in juice, different yeast strains, ambient light, and the addition of external hydrogen peroxide on the response of the potential are presented. Recent examples of controlling the redox potential during white wine and red wine fermentation at a commercial scale are presented, and areas for future research are identified.